Pendampingan Pemasaran Melalui Perbaikan Kemasan Produk Makanan Ringan Pengusaha Kecil di Semarang Utara - Samuel Bintang Nugroho; Marino Adhityawan; Dwi Hayu Agustini (Universitas Katolik Soegijapranata, 2019)
Packaging is an element of product strategy that is used to attract consumers to buy the product. Small businesses usually do not pay attention to their product packages so that the products are not attractive to the target consumers. Here, we used packaging to help the small business partners to leverage sales of their products. The assistance covers labelling in which relevant information about the products is provided to the consumers. The small business partners have been successfully selling their products with higher price because of better packages.